Implementation of Augmented Reality as an Information Media for the Collection of the Popa-Eyato Museum - Amali, Lanto Ningrayati; Husain, Wirahman Salsabil; Kaluku, Moh. Ramdhan Arif; Suhada, Sitti (Jambura Journal of Informatics, 2022)
Museums are facilities that display historical objects and provide information to the public and visitors. However, the presentation of information in the museum to the visitors is far from proper due to the lack of details. The guides provided in the museum are not quite engaging. More than that, the information provided is only in the form of a sheet of paper stuck in the collection. This present study aims to develop information media using augmented reality technology. The method used in this research was the Multimedia Development Life Cycle (MDLC), which had six stages, viz. concept, design, material collecting, manufacture, testing, and distribution. This research develops an application that works as a medium of information related to museum collections using augmented reality, which is more interactive and visitors can use to obtain information from the collection. In addition, this application can visualize 3D and in real-time ethnographic objects in the museum.